Protective vaccinations during pregnancy - adult Poles knowledge in this area - Józefa Dąbek; Oskar Sierka; Halina Kulik; Zbigniew Gąsior (BMC, 2021)
Abstract Background The vaccine is a preparation of biological origin containing antigens that stimulate the body's immune system to produce acquired immunity. Vaccines can contain killed or "live" (attenuated) microorganisms as well as fragments of these (antigens). Although many vaccines are used routinely in pregnancy to provide a seroprotective immune response for mother, fetus and neonate there is much controversy over their use during this unique time. The aim of the study was to find out about the knowledge of adult Poles on the use of preventive vaccinations during pregnancy. Methods The study involved 700 people (100%) aged 18 to 80 years ( x ¯ $$ \overline{x} $$ = 32.16 ± 16.46). Most of the respondents were women (511; 73%). The study consisted of 9 questions about preventive vaccinations of pregnant women and 5 questions about members of the studied group. The aforementioned questions formed the basis of the preparation of the presented article. Results A significant part of respondents (322; 46%) did not have knowledge on the topic of safeness of using preventive vaccinations during pregnancy, 196 (28%) respondents believed that such procedure is not safe. Most of the respondents (371; 53%) did not know about the possibility of using "live" vaccines during pregnancy. 14 (2%) of respondents believed that pregnancy should be terminated in case of administration of a "live" vaccine to a pregnant woman. According to 294 (42%) respondents, vaccinations with "live" vaccines should be completed at least 3 months before the planned pregnancy. The subjects were not aware of the issue of post-exposure vaccination against tetanus and rabies among pregnant women. The respondents' responses were divided on the issue of the safest trimester of pregnancy for vaccine administration. Almost 1/3 of the respondents (203; 29%) indicated the third trimester as the safest for their performance. Conclusion The knowledge of the surveyed group, the majority of whom were women, about the use of vaccinations before and during pregnancy was unsatisfactory. There is a need to educate the public about the benefits and risks of performing or avoiding preventive vaccinations during pregnancy.